Continuous Canopy Shake Mechanical Harvesting Systems - Stephen H. Futch; Fritz M. Roka (EDIS)
Mechanical harvesting systems harvested more than 17,000 acres of Florida citrus in the 2002-03 season. Two types of mechanical harvesters are being used today: continuous canopy shake and trunk shake systems. Continuous canopy shake systems will be discussed in this article and trunk shake harvesting systems will be discussed in other documents. This document is HS1006, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published March 2005.